Multidimensional voiceprint feature assessment system for identifying the depression in children and adolescents: a diagnostic test - Luo, Jie; Liu, Mengqi; Feng, Lihui; Li, Zhaojun; Wu, Yuanzhen; Lu, Jihua; He, Fan (Frontiers in Psychiatry, 2023)
Objective: We design a diagnostic test to evaluate the effectiveness and accuracy of A multidimensional speech feature diagnostic assessment system(MSFDA) versus Hamilton Rating Scale for Depression 24-Item(HAMD-24) for auxiliary diagnosis of child and adolescents with Major depressive disorder(MDD). Methods: This study included 55 child aged 6-16 years who were clinically diagnosed with MDD by DSM-5, and 55 healthy child (typically developing). Each subject completed speech feature capture and was assessed on the HAMD-24 scale by a trained rater. We will calculate the validity indexes, including sensitivity, specificity, Youden's index, likelihood ratio, and other indexes including predictive value, diagnostic odds ratio, diagnostic accuracy and area under the curve [AUC] to assess the effectiveness of the MSFDA system as well as the HAMD-24. Results: The sensitivity (92.73% vs. 76.36%) and the specificity (90.91% vs. 85.45%) of the MSFDA system were significantly higher than the HAMD-24. The AUC of the MSFDA system was also higher than the HAMD-24. There is statistically significant difference between groups(p<0.05), and both of them have high diagnostic accuracy. In addition, the diagnostic efficacy of the MSFDA system was higher than that of HAMD-24 in terms of the Youden index, diagnostic accuracy, likelihood ratio, diagnostic odds ratio and predictive value. Conclusion: MSFDA has performed well in clinical diagnostic trials for identifying MDD in child and adolescents by capturing objective sound features. Compared with the scale assessment method, the MSFDA system deserves to be further promoted in clinical practice for its advantages of simple operation, objective evaluation, and high diagnostic efficiency.